Post hoc analysis of reactogenicity trends between dose 1 and dose 2 of the adjuvanted recombinant zoster vaccine in two parallel randomized trials. Issue 11 (1st November 2020) - Colindres, Romulo; Wascotte, Valentine; Brecx, Alain; Clarke, Christopher; Hervé, Caroline; Kim, Joon Hyung; Levin, Myron J.; Oostvogels, Lidia; Zahaf, Toufik; Schuind, Anne; Cunningham, Anthony L.
ABSTRACT: In two large clinical trials (ZOE-50 [NCT01165177] and ZOE-70 [NCT01165229]), two doses of the adjuvanted recombinant zoster vaccine (RZV) demonstrated >90% efficacy against herpes zoster in adults ≥50 years of age. Solicited adverse events (AEs) were collected for 7 days post-each dose in a study sub-cohort. The incidence of reported solicited AEs was higher for RZV compared to placebo recipients. Since reactogenicity may contribute to a person's willingness to be vaccinated, knowing about expected reactogenicity might help keep high compliance with the second dose. This post hoc analysis assessed the intensity of solicited AEs post-dose 2 reported to the same event's intensity post-dose 1. Intensity was graded from 0 to 3, grade 3 indicating the highest severity. Of the vaccinees who did not experience a specific AE post-dose 1, 72.6–91.7% did not experience the same event after dose 2. Although the frequency of grade 3 AEs post-dose 2 was the highest in participants reporting the same AEs at grade 3 post-dose 1, 65.8–89.3% of vaccinees with grade 3 specific AEs post-dose 1 reported the same AEs at lower intensity post-dose 2. These data can help inform health-care professionals about the frequency and intensity of AEs post-dose 2 with respect to post-dose 1.